Informing Depositors: A Proposed Reform Of The Australian Banking Sector1. Issue 4 (December 2013) - Byford, Martin; Davidson, Sinclair
<x xml:space="preserve">Abstract</x> Financial regulation has the perverse effect of reducing incentives for depositors to monitor the risks banks take. We propose a rating scheme – the Financial Stability Rating – that would work similarly to other product ratings to inform depositors of the risks they face. Our proposal entails greater disclosure of information that is already in the hands of the prudential regulator. There would be no additional regulatory burden on either financial institutions or the regulator. By linking our rating to a formal deposit insurance scheme, depositors would have both the incentive and ability to make informed decisions about the risk return profile of their deposits.